2021
DOI: 10.1590/1678-992x-2020-0172
|View full text |Cite
|
Sign up to set email alerts
|

Biosurfactants synthesized by endophytic Bacillus strains as control of Moniliophthora perniciosa and Moniliophthora roreri

Abstract: Ecuador is responsible for up to 70 % of the world's production of fine flavor cocoa.Although fungal diseases have reduced cocoa production, eco-friendly alternatives have been implemented to control the spread of phytopathogens. This study aimed to explore the potential of endophytic strains isolated from fine flavor Nacional cocoa trees to synthetize compounds with antimicrobial and surface active properties. It was determined that under in vitro conditions, seven strains (DS03, DS07, DS18, DS23, DS31, DS34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…On the other hand, the best PGI against M. roreri was observed for the extract of T. spirale (C10) at 1000 µg/mL (26.20 ± 2.06%) and 100 µg/mL (17.10 ± 1.23%). Higher PGI values (48%) have been reported for culture filtrates from Brazil [ 31 ] and comparable data (15.90–37.10%) for isolates from Mexico [ 20 ] against M. roreri . Differences among results could be attributed to the technique employed since the referenced studies used a dual-culture assay, through which the inoculum size, agar volume, well size, and other variables possibly affect the fungal interactions [ 17 ], isolates, culture filtrates, extracts, or compounds assessed.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…On the other hand, the best PGI against M. roreri was observed for the extract of T. spirale (C10) at 1000 µg/mL (26.20 ± 2.06%) and 100 µg/mL (17.10 ± 1.23%). Higher PGI values (48%) have been reported for culture filtrates from Brazil [ 31 ] and comparable data (15.90–37.10%) for isolates from Mexico [ 20 ] against M. roreri . Differences among results could be attributed to the technique employed since the referenced studies used a dual-culture assay, through which the inoculum size, agar volume, well size, and other variables possibly affect the fungal interactions [ 17 ], isolates, culture filtrates, extracts, or compounds assessed.…”
Section: Resultssupporting
confidence: 63%
“…perniciosa interaction are limited, higher inhibitory activity (75%) affecting mycelial growth and even spore germination of M. perniciosa has been reported for T. harzianum [ 28 ], and significant mycoparasitism levels against M. roreri have been achieved by T. spirale [ 29 ]. In addition, remarkably, antifungal activity against M. perniciosa and M. roreri has been found for foliar endophytic fungi [ 30 ] and endophytic Bacillus [ 31 ] isolated from cocoa cultivars. Additionally, T. spirale has been shown to inhibit the growth of Fusarium oxysporum during in vitro and greenhouse experiments, demonstrating the relevance of the metabolites produced by this strain, which also indicates plant protection against fungal disease [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In previous work, we isolated, identified, and selected B. subtillis DS03 from cocoa crops for producing an organic extract with high surface activity. A preliminary evaluation showed that BCE production was affected by carbon source (e.g., C 6 H 12 O 6 ), nitrogen source (e.g., NaNO 3 ), and phosphate salts (e.g., Na 2 HPO 4 and KH 2 PO 4 ) [ 22 ]. This study evaluated three alternative carbon sources for BCE economic production (i.e., cassava starch, whey, and molasses) according to a new sustainable approach to the biotechnology process.…”
Section: Resultsmentioning
confidence: 99%
“…Bacillus subtilis DS03 strain was isolated from cocoa crops, producing the microbial surfactant [ 22 ]. The medium used for BS production was MMI (20 g/L dextrose, 1 g/L yeast extract, 8.5 g/L NaNO 3 , 5.7 g/L Na 2 HPO 4 , 4 g/L KH 2 PO 4 , 0.21 g/L MgSO 4 7H 2 O, 0.01 g/L FeSO 4 7H 2 O, and 7 × 10 −6 g/L CaCl 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation